Conceptualizing belonging. (June 2013) - Mahar, Alyson L.; Cobigo, Virginie; Stuart, Heather
<x xml:space="preserve">Abstract</x> Purpose: To develop a transdisciplinary conceptualization of social belonging that could be used to guide measurement approaches aimed at evaluating the effectiveness of community-based programs for people with disabilities. Method: We conducted a narrative, scoping review of peer reviewed English language literature published between 1990 and July 2011 using multiple databases, with "sense of belonging" as a key search term. The search engine ranked articles for relevance to the search strategy. Articles were searched in order until theoretical saturation was reached. We augmented this search strategy by reviewing reference lists of relevant papers. Results: Theoretical saturation was reached after 40 articles; 22 of which were qualitative accounts. We identified five intersecting themes: subjectivity; groundedness to an external referent; reciprocity; dynamism and self-determination. Conclusion: We define a sense of belonging as a subjective feeling of value and respect derived from a reciprocal relationship to an external referent that is built on a foundation of shared experiences, beliefs or personal characteristics. These feelings of external connectedness are grounded to the context or referent group, to whom one chooses, wants and feels permission to belong. This dynamic phenomenon may be either hindered or promoted by complex interactions between environmental and personal factors.